Are Written Syntax Features Related to Writing Quality? An Examination of Spanish and English Compositions by Bilingual Children. - Wolters, Alissa Patricia; Kim, Young-Suk Grace (Journal of Speech, Language & Hearing Research, 2024)
Purpose: There is limited research on the writing of young Spanish-English bilinguals and their writing in both languages. In the current study, we addressed whether written syntax features differed by language (English and Spanish) and varied as a function of grade level, English learner status, and instructional program (dual or English immersion). We also examined whether Spanish and English syntax features were related cross-linguistically and related to writing quality within languages and whether these relations to writing quality were moderated by grade level, English learner status, and instructional program. Method: We examined written syntax features of Spanish and English essays by simultaneous and emergent bilinguals in Grades 1, 2, and 3 in either Spanish-English dual immersion or English immersion instruction in the United States (N = 278). Essays were scored for quality and evaluated for mean length of T-units, number of verbs, number of noun agreement words, and number of subject agreement words accurately conjugated. Results: Written syntax features significantly differed by language and varied as a function of grade level, English learner status, and instructional program. Grades 2 and 3 wrote longer utterances, more verbs, and greater noun agreement accuracy than Grade 1. Syntax features were related to writing quality within languages, but Spanish relations were weaker for English learners than non-English learners and for dual immersion students than English immersion students. Conclusion: Our findings suggest written syntax features may be useful for evaluation of English-Spanish simultaneous and emergent bilinguals' writing.